Social support and self-care outcomes in adults with diabetes: The mediating effects of self-efficacy and diabetes distress. Results of the second diabetes MILES – Australia (MILES-2) study. (August 2020) - Chan, Carina K.Y.; Cockshaw, Wendell; Smith, Kimberley; Holmes-Truscott, Elizabeth; Pouwer, Frans; Speight, Jane
Highlights: Social support improves diabetes self-care via self-efficacy and reduced distress. Social support is associated with greater self-efficacy across all diabetes types. Social support is associated with lower distress across all diabetes types. Diabetes distress is an important mediator for glycemic control for insulin-treated diabetes. Future research should disaggregate the components of diabetes social support. Abstract: Aims: Diabetes self-care outcomes are positively impacted by social support. Understanding the mechanisms involved can inform more effective interventions. This study tested potential cross-sectional mediation of social support through self-efficacy and diabetes distress for self-care and clinical outcomes (diet, physical activity, blood glucose monitoring, HbA1c ). Method: We analysed a sub-sample of the Australian Diabetes MILES-2 cross-sectional online survey ( N  = 1727). Measures were: Diabetes Social Support Scale, Confidence in Diabetes Self-care Scale, Problem Areas In Diabetes scale, diet and physical activity subscales of the Summary of Diabetes Self-Care Activities, and self-reported HbA1c . Separate mediation path models were tested for each of the four self-care/clinical outcomes in groups with type 1 and type 2 (insulin- and non-insulin-treated) diabetes. Results: Social support was associated with more optimal self-care and self-reported HbA1c outcomes. When diabetes-specific self-efficacy and distress were included as mediators, the direct path from social support became non-significant. Conversely, the indirect effects of social support through diabetes-specific self-efficacy and distress were significant across all diabetes groups and outcomes. Conclusion: Diabetes-specific self-efficacy and distress may be important mechanisms linking social support with diabetes self-care and clinical outcomes. Social support interventions could explore whether improving diabetes self-efficacy and decreasing diabetes distress could help improve self-care.